Repair of soft tissue defects in finger, thumb and forearm: less invasive methods with similar outcomes. (December 2018) - Elliot, David; Adani, Roberto; Hyun Woo, Sang; Bo Tang, Jin
We review recent developments in using occlusive dressings, dermal templates, and venous flaps for less invasive approaches to treat soft tissue defects of the forearm and fingers. Occlusive dressings can be used for thumb tip or fingertip trauma with soft tissue defects of small or moderate sizes. They permit skin regeneration without use of skin graft or a flap transfer. This is currently a popular way to treat tip soft tissue defects in European countries. Extensive soft tissue defects in the thumb, fingers, hand and forearm require flap transfers traditionally, but in recent years, surgeons use dermal templates to cover the defect site to allow regeneration of subcutaneous tissues, over which a skin graft is used in lieu of a flap. Transfer of a venous flap is currently a reliable procedure and is less invasive compared with conventional flaps, which usually damage a named artery in the donor. We advocate that less invasive methods should be considered for soft tissue defects in the hand and forearm.